Vegetation microclimate and plant physiological responses to climate change experiments in the high and low Arctic - Sullivan, Patrick F., author (Colorado State University. Libraries, 2005)
Recent and projected changes in the Arctic climate are amplified relative to temperate and tropical regions. Vegetation microclimate and plant physiology were examined along natural and experimental gradients in the High and Low Arctic to assess extant variability and sensitivity to climate change. Experimental warming increased early season growth rates of Eriophorum vaginatum, but rates declined to ambient levels by mid-season. There was no evidence that warming increased annual production, above- or below-ground, despite higher rates of early season growth. This observation is consistent with the hypothesis that carbon supply limits the rate of arrival at peak biomass, while nutrients limit the magnitude of annual production. Experimental increases in winter snow depth led to changes in the physiology of two arctic evergreens that were dependent upon species and ecosystem type. Leaf oxygen isotope and nitrogen analyses revealed qualitatively similar effects of deeper snow on the two species, but the effects differed across ecosystems. Leaf carbon isotope analyses revealed that changes in snowmelt water inputs and leaf nutrient concentrations, which differed across ecosystems, had divergent effects on the gas exchange physiology of the two evergreen species. Experimental additions of long-wave radiation and water had effects on the vegetation microclimate that were consistent with expectations and other effects that were unexpected. Infrared lamps warmed the canopy and soils of prostrate dwarf-shrub herb tundra. Greater penetration of supplemental heat to depth was observed when combined with water supplements. Supplemental water did not, however, raise soil water contents. Wind was an important determinant of soil temperatures under ambient conditions and an important modulator of infrared warming. Leaf gas exchange physiology of Salix arctica varied across landscape gradients and in response to supplemental infrared radiation. Soil temperature was an important determinant of stomatai conductance. Variation in stomatai conductance was faithfully recorded in the oxygen isotope ratios of leaf cellulose, when variation in the isotopic composition of source water was removed. Changes in carbon isotope ratios attributable to changes in photosynthetic capacity and those attributable to changes in stomatal conductance were successfully identified when the information contained in carbon and oxygen isotope ratios was combined.
Keywords: ecology; environmental science; botany